(3EOGQI GdehGO h GdeTJQjGJ (B:s (3efgL cej (B/s - (3eMeO, MGce eMSfs; (3GdaVd, eDjO s ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2010)
(3eaGgje YGeI aj EOGQI GdehGO hGdeTJQjGJ(B- (3EgJeGeGJ hEQJHGWGJ EOGQI GdehGO hGdeTJQjGJ(B- (3JbOjQ GdWdH(B- (3GdSjWQI Ydi GdNRjf(B- (3eUGOQ GdJLgjR(B- (3Gdfbd GdeGOj(B- (3Gdfbd GdOGNdj hJUeje GdeNGRf(B- (3TQGA GdehLhOGJ GdQCSeGdjI(B- (3GdehGRfGJ GdJbOjQjI ddehGO hGdeTJQjGJ(B- (3GdNjGQGJ GdESJQGJjLjI dEOGQI GdehGO hGdeTJQjGJ(B- (3fXGe eYdheGJ EOGQI GdehGO hGdeTJQjGJs
Keywords: (3EOGQI GdEfJGLs; (3EOGQI GdeTJQjGJs; (3GdEOGQI GdUfGYjIs